The role of executive functioning in memory performance in pediatric focal epilepsy. (23rd January 2017) - Sepeta, Leigh N.; Casaletto, Kaitlin Blackstone; Terwilliger, Virginia; Facella‐Ervolini, Joy; Sady, Maegan; Mayo, Jessica; Gaillard, William D.; Berl, Madison M.
Summary: Objective: Learning and memory are essential for academic success and everyday functioning, but the pattern of memory skills and its relationship to executive functioning in children with focal epilepsy is not fully delineated. We address a gap in the literature by examining the relationship between memory and executive functioning in a pediatric focal epilepsy population. Methods: Seventy children with focal epilepsy and 70 typically developing children matched on age, intellectual functioning, and gender underwent neuropsychological assessment, including measures of intelligence (Wechsler Abbreviated Scale of Intelligence [WASI]/Differential Ability Scales [DAS]), as well as visual Children's Memory Scale (CMS Dot Locations) and verbal episodic memory (Wide Range Assessment of Memory and Learning [WRAML] Story Memory and California Verbal Learning Test for Children [CVLT‐C]). Executive functioning was measured directly (WISC‐IV Digit Span Backward; Clinical Evaluation of Language Fundamentals, Fourth Edition (CELF‐IV) Recalling Sentences) and by parent report (Behavior Rating Inventory of Executive Function [BRIEF]). Results: Children with focal epilepsy had lower delayed free‐recall scores than controls across visual and verbal memory tasks (p = 0.02; partial η 2 = 0.12). In contrast, recognition memory performance was similar for patients and controls (p = 0.36; partial η 2 = 0.03). Children with focal epilepsy demonstrated difficulties in working memory (p = 0.02; partial η 2 = 0.08) and planning/organization (p = 0.02) compared to controls. Working memory predicted 9–19% of the variance in delayed free recall for verbal and visual memory; organization predicted 9–10% of the variance in verbal memory. Patients with both left and right focal epilepsy demonstrated more difficulty on verbal versus visual tasks (p = 0.002). Memory performance did not differ by location of seizure foci (temporal vs. extratemporal, frontal vs. extrafrontal). Significance: Children with focal epilepsy demonstrated memory ability within age‐level expectations, but delayed free recall was inefficient compared to typically developing controls. Memory difficulties were not related to general cognitive impairment or seizure localization. Executive functioning accounted for significant variance in memory performance, suggesting that poor executive control negatively influences memory retrieval.